Processing of mercury-based superconducting wires and tapes. - Khaliq, M; Yang, G; Shields, T; Abell, J; Peacock, G; Gameson, I; Edwards, P (Minerals, Metals and Materials Soc (TMS), 1996)
We have produced silver-sheathed HgBa2CuO4+δ (Hg-1201) superconducting tapes exhibiting a transition temperature of 96 K. Progress in the synthesis of these tapes was achieved by heat treating off-stoichiometric mixtures of oxides in the silver sheath, air-quenching the samples and the novel use of thermal cycling. Superconducting properties were assessed by SQUID and a.c. susceptibility measurements. Phase purity, texture and morphology of the samples were investigated using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The majority of the material inside the tapes was superconducting but not sintered. A thin layer of material adjacent to the silver-sheath was sintered; however, it was found to be non-superconducting. Quenching was necessary after every firing in the thermal cycling process to obtain superconductivity in these tapes.